2009
DOI: 10.1371/journal.pone.0005671
|View full text |Cite
|
Sign up to set email alerts
|

Small Interfering RNA Targeting M2 Gene Induces Effective and Long Term Inhibition of Influenza A Virus Replication

Abstract: RNA interference (RNAi) provides a powerful new means to inhibit viral infection specifically. However, the selection of siRNA-resistant viruses is a major concern in the use of RNAi as antiviral therapeutics. In this study, we conducted a lentiviral vector with a H1-short hairpin RNA (shRNA) expression cassette to deliver small interfering RNAs (siRNAs) into mammalian cells. Using this vector that also expresses enhanced green fluorescence protein (EGFP) as surrogate marker, stable shRNA-expressing cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 41 publications
2
35
0
1
Order By: Relevance
“…94 Sui et al also reported that inhibition of propagation of H1N1 and HPAI H5N1 viruses in stable cell lines by siRNAs targeting the M2 gene was sustained for more than 50 hours post-infection. 79 Similar results were obtained by Ge et al in MDCK cells using siRNA targeting the NP gene (NP-1496). 66…”
Section: Broad Anti-influenza Spectrum and Long-term Inhibitory Effectsupporting
confidence: 81%
See 2 more Smart Citations
“…94 Sui et al also reported that inhibition of propagation of H1N1 and HPAI H5N1 viruses in stable cell lines by siRNAs targeting the M2 gene was sustained for more than 50 hours post-infection. 79 Similar results were obtained by Ge et al in MDCK cells using siRNA targeting the NP gene (NP-1496). 66…”
Section: Broad Anti-influenza Spectrum and Long-term Inhibitory Effectsupporting
confidence: 81%
“…79 Another study also revealed that siRNAs could effectively reduce the NS1 gene expression of the H5N1 avian influenza virus. 97 Sirnaomics have developed a siRNA-based therapeutic agent against influenza virus, known as STP702.…”
Section: Possibility Of Use As Anti-influenza Agent In Human and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ge et al also showed that shRNA, expressed by a lentivirus DNA vector, could prevent influenza A/Puerto Rico/8/34-induced pneumonia in mice. A number of subsequent studies have shown that siRNA targeting different RNA segments can inhibit the replication of highly pathogenic avian influenza virus H5N1 [10, 12, 13] and various influenza A (H1N1) viruses in vitro and in vivo [9, 11, 2123]. …”
Section: Discussionmentioning
confidence: 99%
“…The sequence-specific knockdown of viral genes in infected cells without affecting on host gene expression has generated great interest in development of small interfering RNAs (siRNAs)-based antiviral therapeutics (Elbashir et al 2001;Morris and Rossi 2006). Previous reports have shown that the siRNAs could effectively inhibit IAV replication both in vivo and in vitro (Ge et al 2003;Li et al 2005;Zhou et al 2007;Sui et al 2009;Zhang et al 2009;Li et al 2011).…”
Section: Introductionmentioning
confidence: 99%